1996
DOI: 10.1007/bf02245607
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone: regional effects in vivo on release and metabolism of dopamine and serotonin in the rat brain

Abstract: The antipsychotic drug risperidone shows high affinity for both central serotonin (5-HT)2A and dopamine (DA)-D2 receptors in vivo. By employing microdialysis in freely moving rats, the effects of acute risperidone administration on regional brain DA and 5-HT release and metabolism were compared with the corresponding effects of the atypical antipsychotic drug clozapine as well as amperozide, the selective DA-D2 receptor antagonist raclopride and the selective 5-HT2A/5-HT2C receptor antagonist ritanserin. Rispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
58
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 54 publications
7
58
0
Order By: Relevance
“…This effect may have been mediated, at least partially, by blockade of local 5-HT2A receptors, since cortical M100907 induced a similar effect. It is unknown whether cortical risperidone infusion, as used in the current work, would increase 5-HT levels in the mPFC as has been Serotonin-2A receptors and prefrontocortical dopamine release EA Pehek et al shown with systemic risperidone treatment (Ichikawa et al, 1998;Hertel et al, 1996; although see Zhang et al, 2000;Ojima et al, 2004). If so, other non-5-HT2 serotonin receptors could be implicated in this stress effect of risperidone.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This effect may have been mediated, at least partially, by blockade of local 5-HT2A receptors, since cortical M100907 induced a similar effect. It is unknown whether cortical risperidone infusion, as used in the current work, would increase 5-HT levels in the mPFC as has been Serotonin-2A receptors and prefrontocortical dopamine release EA Pehek et al shown with systemic risperidone treatment (Ichikawa et al, 1998;Hertel et al, 1996; although see Zhang et al, 2000;Ojima et al, 2004). If so, other non-5-HT2 serotonin receptors could be implicated in this stress effect of risperidone.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, this combination of properties may explain why the systemic administration of higher doses (1 mg/kg) of risperidone produces increases in mPFC DA efflux (Hertel et al, 1996;Kuroki et al, 1999;Zhang et al, 2000). Lower doses of risperidone (0.004 mg/ kg), like M100907, do not alter cortical DA efflux (Westerink et al, 1998(Westerink et al, , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, risperidone and clozapine may be able to increase DA release in the medial prefrontal cortex. Apparently consistent with this possibility, a recent study proposed that risperidone and clozapine could increase DA release in the medial prefrontal cortex (Hertel et al, 1996;Kuroki et al, 1999;Ichikawa et al, 2001). Moreover, these effects of atypical antipsychotics are through D2 and 5-HT2A receptors blockade (Ichikawa et al, 2001).…”
Section: Discussionmentioning
confidence: 87%
“…The present study shows that clozapine and other putative atypical neuroleptics dose-dependently increase extracellular DA in the BNST; whereas, haloperidol and Clozapine increased DA in dialysates from BNST at doses lower than those effective in raising DA concentration in dialysate from the prefrontal cortex (Nomikos et al 1994;Volontè et al 1997); risperidone raised DA in the BNST only at doses about twofold higher than those active in increasing dialysate DA in the prefrontal cortex (Hertel et al 1996;Volontè et al 1997). Olanzapine, BIMG 80, and amperozide, instead, were equipotent in increasing DA in dialysates from the BNST and from prefrontal cortex (Nomikos et al 1994, Volontè et al 1997, Xi-Ming et al 1998).…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, an increase of DA transmission onto specific DA receptor subtypes might be instrumental for the antipsychotic effects of atypical neuroleptics. Similar considerations have been applied to the increase of DA release in the prefrontal cortex, which apparently behaves in a manner similar to the BNST in response to atypical neuroleptics (Andersson et al 1995;Hertel et al 1996;Volontè et al 1997). It is notable, however, that typical neuroleptics increase, although to a lesser extent, extracellular DA in the prefrontal cortex whereas, they are without effect in the BNST.…”
Section: Discussionmentioning
confidence: 83%